Developing the innovation potential of SMEs on the example of a medium sized family business functioning in a global supply chain = Rozwój potencjału innowacyjnego MŚP na przykładzie przedsiębiorstwa rodzinnego funkcjonującego w globalnym łańcuchu dostaw - Dzikowski, Piotr (Zielona Góra: Faculty of Economics and Management Press)
Most domestic companies from the SME sector cannot afford to bear the risk of unsuitable technological, market and financial decisions related to innovation activities. The risk of failure can be significantly reduced by entering into a cooperation with customers standing at a much higher level of innovative development. The main goal of this article is to describe the process of gradually increasing the innovative capacity of the Polish family business that has been achieved through the cooperation within the global industrial chain operating in the field of public service vehicle industry.
Keywords: innowacyjnośc w sektorze MŚP; przedsiębiorstwa rodzinne; ryzyko inwestycyjne; przedsiębiorstwa komunikacji publicznej; innovation potential of SMEs; family business; public service vehicle industry